The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.5194/hess-12-77-2008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rainfall observation network on model calibration and application

Abstract: Abstract. The objective in this study is to investigate the influence of the spatial resolution of the rainfall input on the model calibration and application. The analysis is carried out by varying the distribution of the raingauge network. A meso-scale catchment located in southwest Germany has been selected for this study. First, the semi-distributed HBV model is calibrated with the precipitation interpolated from the available observed rainfall of the different raingauge networks. An automatic calibration … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 28 publications
9
104
0
Order By: Relevance
“…Results of the simulation confirmed the most important findings of the analysis at event scale, in agreement with Bardossy et al (2008). Fig.…”
Section: Hydrograph Reconstructionsupporting
confidence: 79%
See 1 more Smart Citation
“…Results of the simulation confirmed the most important findings of the analysis at event scale, in agreement with Bardossy et al (2008). Fig.…”
Section: Hydrograph Reconstructionsupporting
confidence: 79%
“…As an example, Schuurmans et al (2007) showed that the spatial variability of daily rainfall has a major effect on discharge and spatial distribution of groundwater level and soil moisture content of the catchment. More recently, studies based on continuous simulations have also been carried out (Bardossy et al 2008), confirming that an excessive reduction of rain gauges, up to a certain threshold number, makes model performances worse. Meselhe et al (2009), using a physically based and conceptual hydrologic model, showed that an increase in the rain gauge density or the rainfall data temporal resolution caused a significant improvement of the hydrograph estimation.…”
Section: Introductionmentioning
confidence: 95%
“…Krajeski et al (1991) also conclude that for the analysis of spatial problems, fully-distributed models may be more suitable and recommend those for further studies. Bárdossy and Das (2008) point out that with an increasing spatial resolution of the applied rainfall-10 runoff model, the sensitivity of for example the rain gauge density and hence the spatial rainfall patterns may increase as well. The rainfall-runoff simulations were carried out with two models, the semi-distributed HBV model and the fullydistributed WaSiM-model.…”
Section: Discussion Of Rainfall-runoff Simulation Resultsmentioning
confidence: 99%
“…WaSiM) lead to numerical diffusion and hence to a "smudging" of the areal rainfall, resulting in less differences in runoff statistics. Other investigations raise the question if spatial rainfall patterns can be transferred sufficiently into runoff with semi-distributed models and thus with a coarse spatial resolution (Krajeski et al, 20 1991, Obled et al, 1994, Bárdossy and Das, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall is regarded as the key driving input of hydrological models and it is impossible to produce accurate runoff predictions if forced with inaccurate rainfall data [11]. The impact of spatial and temporal error in predicting rainfall on predicted flow has been highlighted by many researchers [12][13][14][15]. Currently, rainfall data from rainfall stations are still indispensable because the station data are regarded to be relatively accurate and more reliable than the radar data at the point where a station locates [16,17].…”
Section: Introductionmentioning
confidence: 99%